Relación entre el porcentaje de grasa corporal y el índice de masa corporal en la evaluación de sobrepeso y obesidad en adultos atendidos en el Hospital Regional de Loreto, 2025 - Agustín Vázquez, Juan Diego (2025)
The present study aimed to determine the relationship between Body Fat Percentage (%BF) and Body Mass Index (BMI) in the assessment of overweight and obesity in adults attended at the Regional Hospital of Loreto during the year 2025. It was an observational, descriptive, cross-sectional study with a correlational design, involving a study population of 410 adults attended at the Regional Hospital of Loreto in 2025. An anthropometric evaluation form was applied, which included measurements of weight, height, waist circumference, and body fat percentage corresponding to the sample. SPSS software version 27 was used for statistical analysis, and data analysis was performed using the non-parametric Spearman's Rho test (ρ), with a significance level of p≤0,05. The main findings showed that 78,5% of the total sample presented a very high risk associated with %BF, identified in 99% of women and in 86,4% of individuals aged 20 to 39 years. Additionally, 93,5% were classified as obese according to BMI, identified in 96% of men and in 98% of individuals aged 40 to 59 years. Spearman's correlation (ρ) yielded a value of r=0,808, indicating a high positive correlation between BMI and %BF; moreover, the study variables were statistically significant (p=0,000). The study concluded that there is a high positive correlation between body mass index (BMI) and body fat percentage (%BF), and that body fat percentage is more specific for the diagnosis of overweight and obesity in adults attended at the Regional Hospital of Loreto.